Implementasi ISAK 35 Pada Laporan Keuangan Panti Asuhan - Beti Setiawati; Diska Arliena Hafni (Jurnal Akuntansi dan Governance, 2023)
This study aims to analyze the application of ISAK 35 to the financial reports of the Muhammadiyah Orphanage of Nanggulan-Kulonprogo. This study employs qualitative descriptive analysis. Data were obtained through observation, interviews, and documentation at Muhammadiyah Orphanage of Nanggulan-Kulonprogo. The results show that the Muhammadiyah Orphanage of Nanggulan-Kulonprogo has not presented accountable financial reports and has not implemented ISAK 35. The financial reports in place are only monthly report of cash receipts and disbursements, also not annually accumulated. Thus, it is guided that the preparation of the financial statements of the Muhammadiyah Orphanage of Nanggulan-Kulonprogo should be based on ISAK 35 includes the Statements of Financial Position, Reports of Comprehensive Income, Reports of Changes in Net Assets, Statements of Cash Flows and Notes to Financial Statements